Analisis Faktor yang Berpotensi Mempengaruhi Pembelian Kosmetik pada Platform E-Commerce - T, Miftahur Rahmi Anasti; Saputra, Indra (Lembaga Yasin AlSys, 2025)
This study aims to analyze the factors influencing online cosmetic purchasing decisions. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that platform, price, and marketing factors have a direct influence on purchasing decisions for cosmetics on e-commerce platforms, while social, product, and personal factors do not exhibit a direct effect. Additionally, platform and marketing factors indirectly influence purchasing decisions through the mediation of personal factors, whereas social, price, and product factors are not mediated by personal factors. These findings highlight that platform technical aspects, pricing strategies, and digital marketing are the primary determinants of online cosmetic purchasing decisions, while social influences and product characteristics require additional strategies to effectively impact consumer decision-making.